The essential management toolbox : tools, models and notes for managers and consultants - Burtonshaw-Gunn, Simon A. (Chichester, England ; Hoboken, NJ : J. Wiley & Sons, 2008)
"The purpose of this book is not to short-cut any formal learning and understanding of the use of established and practical management tools and techniques but to provide an easy access to various management approaches through a collection of models and brief prompting notes. As such this book will be of value for practising managers, students and management consultants, whether undertaking assignments for external clients or working within their own organizations in an advisory, capacity. The book not only supports the Institute of Business Consulting's Certificate and Diploma programmes but also provides a wide range of models and brief notes on over twenty recognizable skill sectors within management fields and specialisms."--Jacket
Business planning -- Change management -- Customer relationship management -- Decision making and problem resolution -- Financial management -- International management -- Marketing management -- Organizational development -- People-focused performance management -- Process improvement -- Product management -- Project management -- Quality management -- Risk management -- Strategic management -- Supply chain management -- Time management -- Undertaking research -- Working as a management consultant -- Workshop facilitation.
Includes bibliographical references (pages 349-354) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Management; Gestion; management; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Management; Management; gestion d'entreprise -- manuel; consultant -- gestion d'entreprise -- manuel